State of exception on a comparative scale. Notes of Argentinian, Chilean and Uruguayan cases throughout the 1950s (Quinto Sol, 2015)
This article outlines the use of state of emergency measures as an instrument of democratic governments in the Southern Cone during the 1950s, when the political situation enabled the authorities to suspend the rule of law, totally or partially, in cases deemed as a threat to internal order. The application of such measures at once generates a situation in which the governments’ measures are legitimized by a force that is both within and outside the legal framework, and which leads to those perceived as dangerous being seen as enemies of the political system. To this end, we have adopted a comparative historical approach to the use of state of emergency measures in Argentina, Chile and Uruguay, taking three situations as representative examples of each case. By means of a comparative study we show how the patterns of logic and political practice specific to each country are far from normal or clear and require explanation. In addition we have sought to identify what the three cases have in common, that permit us to consider, on the one hand, certain political aspects that can be understood as characteristic of the resort to states of emergency and, on the other, to explain historical aspects both specific to the period in question and more generic as well.
Keywords: state of emergency; democracy; Argentina; Chile; Uruguay